Identifying Customer Segmentation Models for FinTech & Finding the Consumer Behavioral Difference through a Study of Payment Instruments & E-commerce in Indian Market - Agrawal, Vivek (Global journal of Business and Integral Security, 2024)
Background The Advent of Fintech payment instruments has led to significant discussions around customer shifts from Credit cards to Fintech products especially BNPL and UPI, both for E-commerce & POS. This discussion has been the focus point of various industry reports considering the meteoric increase in payment methods innovations, investments, and number of companies. With limited academic research to fully understand this difference across the world, there exists a gap in defining the finite customer segmentation for various payment instruments. As per the extensive research done by the author, this study is one of the first such research in Indian geographical limits. Additionally, the impact of these fintech products on E-commerce consumer behaviour and an understanding of differentiated customer segmentation for E-commerce with an absolute vacuum for Indian territory. Methods This research has used K-Means Clustering & Hierarchical Clustering for the identification & classification of principle variables for the payment Instruments & E-commerce. PLS-SEM is used to understand the relationship strength between these variables and validate the model proposed. Results Trust, Performance Expectancy, Effort Expectancy, Social Influence, and Facilitating Conditions are found to have strong impact on the customer purchase intentions using all digital payment mode. vii Payment Preference of a customer strongly affect all the above parameters in addition to having a strong impact on customer purchase behaviour. The study found a strong impact of rewards and discounts on customer Purchase intentions and choice of payment methods. Tech attributes like widespread availability, UI/CX, merchant acceptance, 1-click payment, ease of payment, and high security features have a strong impact on customer payment preference and indirect effect on customer purchase intentions. Payment Preference is also affected by government policies and geopolitical factors who have significant indirect effect on customer purchase intention. Demographic factors Age, Gender, and Income, along with Type and value of purchase also impacts choice of payment method differently. While Credit Card and Digital Wallet uptake increases with increase in Age and Income, there exist a negative relationship between BNPL and Debit Card / Internet banking with Age and Income. Discussion and Conclusion During the process, the research also creates the first true academic framework for Payment method customer segmentation from an Indian perspective which can also be replicated across other geographies. The author proposes a STATE model for gauging the impact of payment methods on Ecommerce comprising of Service Benefit Expectations, Type of Customer, Attributes of Tech, Type of Purchases, and External Factors and communication.